Review of photocatalytic and photo-electrocatalytic reduction of CO2 on carbon supported films. (22nd August 2022) - Dhabarde, Nikhil; Selvaraj, Josephine; Yuda, Afdhal; Kumar, Anand; Subramanian, Vaidyanathan Ravi
Abstract: CO2 capture/conversion is one of the biggest challenges facing humanity. This review reports on the analysis of the research performed over the last five years on the application of carbon-based materials as supports for CO2 conversion using the photo (electro)catalytic approach. Three types of photocatalyst materials – metals, metal-oxides, non-oxides, and their combinations with carbon are presented. Our focus has been on i) carbon – based structures and their unique features that assist with photocatalysis, ii) the approaches to consider for photo (electro)catalytic CO2 conversion, iii) representative examples of different carbon allotrope supported composites for CO2 conversion, and iv) tools to perform quantitative estimation of their performance. We have provided insights into the benefits of reduced graphene oxide (rGO) based on our team's research and listed the areas where not only improvement in CO2 reduction reactions can be considered but also areas of interest in other applications where rGO can be leveraged in a beneficial manner. Highlights: Carbon supports significantly boost photocatalysis and photoelectrocatalysis. CO2 conversion using several photo-driven carbon supported composites demonstrate wide ranging C1 and C2 products. Thermochemical treatment of rGO can maximize CO2 conversion using photoactive materials.